Understanding exposures and latent disease risk within the National Institute of Environmental Health Sciences Superfund Research Program - Amolegbe, Sara M; Carlin, Danielle J; Henry, Heather F; Heacock, Michelle L; Trottier, Brittany A; Suk, William A (Experimental biology and medicine (Maywood, N.J.), 2022)
Understanding the health effects of exposures when there is a lag between exposure and the onset of disease is an important and challenging topic in environmental health research. The National Institute of Environmental Health Sciences (NIEHS) Superfund Basic Research and Training Program (SRP) is a National Institutes of Health (NIH) grant program that uses a multidisciplinary approach to support biomedical and environmental science and engineering research. Because of the multidisciplinary nature of the program, SRP grantees are well-positioned to study exposure and latent disease risk across humans, animal models, and various life stages. SRP-funded scientists are working to address the challenge of connecting exposures that occur early in life and prior to conception with diseases that manifest much later, including developing new tools and approaches to predict how chemicals may affect long-term health. Here, we highlight research from the SRP focused on understanding the health effects of exposures with a lag between exposure and the onset of the disease as well as provide future directions for addressing knowledge gaps for this highly complex and challenging topic. Advancing the knowledge of latency to disease will require a multidisciplinary approach to research, the need for data sharing and integration, and new tools and computation approaches to make better predications about the timing of disease onset. A better understanding of exposures that may contribute to later-life diseases is essential to supporting the implementation of prevention and intervention strategies to reduce or modulate exposures to reduce disease burden.